Teradata SQL 14 macros - Coffing, Tom.; Safari eBooks ([S.I.] : Coffing Studios, 2014)
"This chapter teachers viewers everything about Teradata Macros."--Resource description page
Title from resource description page (viewed Oct. 13, 2014).
Presenter, Tom Coffing.
Keywords: Domain-specific programming languages; Relational databases; SQL (Computer program language); Electronic books